2023
DOI: 10.32604/jrm.2023.026706
|View full text |Cite
|
Sign up to set email alerts
|

Nanolignin, a Coupling Bio-Agent for Wood-Plastic Composites

Abstract: The influence of nanolignin coupling bio-agent on some characteristics of polypropylene-wood flour composites was studied. Thus, nanolignin was prepared by the acidic method, and then different ratios of it (0, 1, 3 and 5 wt%) were added to a polypropylene-wood flour mixture. After mechanically mixing wood flour, nanolignin, and polypropylene, the mixture was injection molded. ASTM methods were used to measure the structural properties of nanolignin, and prepared composites' water absorption, thickness swellin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Decreasing water absorption and thickness swelling of the WPCs by addition of nanolignin can be explained by the hydrophobic nature of nanolignin which acts as a water repellent. 8 Moreover, the cracks and voids which formed in the WPCs manufacturing process were filled with nanolignin and resulted in the prevention of the penetration of water into the inner parts of the composites. Figures 6 and 7 also show that modification of nanolignin by maleic anhydride reduced further water absorption of the composites than unmodified nanolignin.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Decreasing water absorption and thickness swelling of the WPCs by addition of nanolignin can be explained by the hydrophobic nature of nanolignin which acts as a water repellent. 8 Moreover, the cracks and voids which formed in the WPCs manufacturing process were filled with nanolignin and resulted in the prevention of the penetration of water into the inner parts of the composites. Figures 6 and 7 also show that modification of nanolignin by maleic anhydride reduced further water absorption of the composites than unmodified nanolignin.…”
Section: Resultsmentioning
confidence: 99%
“…A comparison between the IR spectra of nanolignin and maleated nanolignin indicated that the intensity of the 1700 cm À1 which is related to the -COOH group increased in the maleated nanolignin, a clear indication of the anhydride ring opening to form maleic acid. 8 The intensity of the 2800 cm À1 band related to the C-O groups and 1200 cm À1 band assigned to the C = C bonds also increase in maleated nanolignin, this again being due to the addition of maleic anhydride. Furthermore, the nanolignin modified with the maleic anhydride showed a smaller peak at 3420 cm À1 (the hydroxyl group) than the virgin nanolignin.…”
Section: Ftir Analysismentioning
confidence: 96%
See 3 more Smart Citations